Study of non-cash transactions, integrity and competence effect on the financial management performance of west sulawesi local government - Ardinah; Maryadi; Sjarlis, Sylvia (Entrepreneurship and Small Business Research, 2022)
This research aims to study the effect of the implementation of non-cash transactions, integrity and competence simultaneously and partially on financial management performance in the West Sulawesi Provincial Government.  This research used survey research. The research was conducted in the West Sulawesi Provincial Government. The research time was conducted from July 2021 to August 2021. The research population is all employees in the West Sulawesi Provincial Government spread across 42 Regional work unit (Satuan kerja perangkat daerah, SKPD). Determination of samples in this study by purposive sampling with the criteria of the Financial Management Officer (Pejabat Penatausaha Keuangan, PPK) and the Treasurer.  The test results showed that partially the variable application of non-cash transactions, integrity and competence had a significant positive effect on financial management performance in the West Sulawesi Provincial Government. The simultaneous variable application of non-cash transactions, integrity and competence has a significant positive effect on the performance of financial management in the West Sulawesi Provincial Government.  Variabel competence has the most dominant influence on financial management performance in the West Sulawesi Provincial Government. The research implies that increasing knowledge, skill, and attitude of civil servant are able to enhance the efficient of financial management of local government.